우리나라 성인의 골감소증 및 골다공증의 유병률 및 위험요인 - 이도연(Do-Youn Lee) (한국콘텐츠학회 논문지, 24(7), 2024)
본 연구는 우리나라 40세 이상 성인의 골감소증 및 골다공증의 유병률과의 위험요인을 파악하고, 질환에 대한 관리를 통하여 예방을 위한 기초자료를 제공하는 것이 목적이다. 국민건강영양조사 2008-2011년도 자료를 바탕으로 40세 이상 성인 중 골밀도 검사와 건강설문조사 등에 참여한 5,903명을 대상자로 선정하였다. 복합표본 다중 로지스틱 회귀분석을 사용하여 골감소증 및 골다공증의 위험요인을 분석하였다. 분석결과 본 연구대상자의 골감소증 유병률은 47.3%로 나타났고, 골다공증은 20.2%로 나타났다. 골감소증 및 골다공증의 공통적인 위험요인으로는 여성일수록, 연령대가 높아질수록, 교육수준과 개인 소득수준이 낮을수록, BMI 기준으로 저체중인 경우로 나타났다. 추가적인 골다공증의 위험요인으로는 배우자와 동거하지 않는 경우, 혈중 비타민 D 수치가 낮은 경우, 현재 흡연자인 경우, 비음주자인 경우 골다공증 위험이 높게 나타났다. 따라서, 골감소증 및 골다공증의 발병을 낮추기 위하여 이러한 위험요인을 가진 대상자를 위한 예방 및 중재 교육이 필요하다. The purpose of this study is to identify risk factors for the prevalence of osteopenia and osteoporosis in adults over 40 years of age in Korea and to provide basic data for prevention through disease management. Based on the data from 2008-2011 of the Korea National Health and Nutrition Examination Survey, 5,903 adults over 40 years of age who participated in bone mineral density tests and health surveys were selected as subjects. Risk factors for osteopenia and osteoporosis were analyzed using complex sample multi-logistic regression analysis, the prevalence of osteopenia in this study subject was 47.3%, and osteoporosis was 20.2%. Common risk factors for osteopenia and osteoporosis were found to be women, higher age group, lower education and individual income level, and underweight based on BMI. Additional risk factors for osteoporosis were those who do not live with their spouse, have low blood vitamin D levels, current smokers, and non-drinkers. Therefore, to reduce the incidence of osteopenia and osteoporosis, prevention and intervention education for subjects with these risk factors is necessary. KCI Citation Count: 0